SWING THE ANGKLUNG TUBE IN THE DIGITAL ECONOMY ERA: BASED ON INTANGIBLE CULTURAL HERITAGE AND INTELLECTUAL PROPERTY RIGHTS PERSPECTIVE - Rafianti, Laina; Suryamah, Aam; Putra, Afrizal Musdah Eka; Ramli, Ahmad M. (Indonesian Journal of International Law, 2021)
After the UNESCO inscription of Angklung as Intangible Cultural Heritage in 2010, the responsibility of the angklung custodian is harder. Angklung is not only must exist as a living culture but must also develop. At first, the inscription of angklung is essential to ascertain cultural identity from Indonesia. Besides, intellectual property law contributes a vital key to protect the community and individuals who create copyrighted subject matter based on angklung. Double protection for angklung in cultural and intellectual property also provides double consequences. The problem is, the relation between those two related institutions is weak. Moreover, the mechanism of protection between communal and individual intellectual proper is overlapping. Although the discussion in the IGC GRTKF is still an ongoing debate, Indonesia has regulated national regulation on TCEs with its problems in implementing legislation. Otherwise, the demand to protect the utilization of Angklung is high in this rapid and massive digital economy era. This article aims to harmonize legal instruments in cultural and intellectual property subject matter to realize comprehensive protection for Angklung and determine the implementation step of protection and utilization of Angklung in the digital economy era after the inscription of the UNESCO. After mapping the legal instruments regarding culture and intellectual property, the researcher concluded that it needs a grounded implementing legislation besides the existing legal instruments. The government cannot achieve the protection alone without willpower and coordination with custodians, artists, and educational institutions in preserving and developing Angklung.